Group facilitation skills for participatory decision-making: report of a follow-up outcome evaluation - Sette, Cristina; Watts, J. (2010)
This working paper reports on an evaluation designed to assess the usefulness of the skills gained during the training course, if the skills learned have been applied and, if so, how the new facilitation tools and techniques have changed meeting processes. The evaluation also identified obstacles to the use of new skills faced by participants, additional follow-on activities that have been conducted by participants, and other related skills that are needed to complement what was learned in the ILAC facilitation course.